What are the significant turning demands of match play of an English Premier League soccer team? - Dos`Santos, T.; Cowling, I.; Challoner, M.; Barry, T.; Caldbec, P. (Journal of Sports Sciences, 2022)
This study aimed to compare the significant turning demands of English Premier League soccer match play relative to playing position using LiDAR technology. Turning data were collected from an English Premier League soccer team (2020-2021 season; 18 fixtures) using a Sportlight® LiDAR tracking system. Turns were tracked during match play, sub-categorised by entry speed (<3.0, 3.0-5.5, 5.5-7.0 and >7.0 m/s) and turning angle (Low: 20-59°; Medium: 60-119°; High: 120-180°). Turning metric frequencies were compared between playing positions (centre backs, full-backs, central midfielders, wide midfielders, and central forwards). On average, per match, central midfielders performed more total turns (~38 vs ~18-27), turns with entry speeds <3.0 (~15 vs ~7-10) and 3.0-5.5 m/s (~21 vs ~8-15) and low (~4 vs ~1-2), medium (~10 vs ~3-6) and high angled turns (~24 vs ~12-18) compared to all other playing positions (p = 0.001, d = 0.96-2.74). Approximately, 90% of turns during matches were performed with entry speeds <5.5 m/s and ~63-70% were high angled turns. This study provides unique insights into the turning demands of English Premier League soccer matches , which can be used to inform position-specific physical preparation strategies, turning testing battery selection, agility drill construction, and rehabilitation and return to play standards.